On Being Orthodox. Moral Parameters for founding the orthodox identity in the Eastern Orthodox Church - Gogovski Stefan (Mitropolitan Library St. John the Theologian - Bitola, 2023)
The purpose of the paper is to research and capture in one synthesis the founding elements of the historical development of the Eastern Orthodox Church, which serve as guidelines for landscaping the formative way of constructing the basis for the Orthodox way of existence since the rising of the Church until today, that are intrinsically bond with the moral way of living in the spirit of the Orthodox faith. In that regard, the paper also focuses on elaborating the keystones of the Eastern Orthodox Ethics - the moral parameters that are essential when the Orthodox identity is in question.
Keywords: Orthodox identity, Christian Ethics, Orthodox Church